Influence of rearing temperature on muscle growth and adipose tissue in Nile tilapia (Oreochromis niloticus) strains - Rondinelle Artur Simões Salomão (Acta Scientiarum. Animal Sciences, 2018)
This study aimed to evaluate the effect of temperature on the tissue growth of Red, GIFT and Supreme tilapia strains. Fingerlings of approximately 1.4 g from male populations were reared for a period of 60 days, in three recirculating systems, each system containing 6 water tanks of 0.5 m³, at three temperatures (22, 28 and 30ºC). Ten fish of each recirculation system and each temperature studied were sampled. Fishes have been anesthetized, euthanized and weighed. The samplings have been done from the dorsal musculature, caudal, visceral and ventral subcutaneous adipose tissue. Histological sections were prepared and evaluated to determine the diameter of the cells. The experimental design was completely randomized factorial 3 X 3 (strain X temperature). Analysis of variance was performed and means were compared. Higher weights were found for fish reared at 30°C (56.23 g) compared to those grown at 28 (42.12 g) or 22°C (10.52 g). The cooled water temperature (22°C) may have contributed to the hypertrophy of white muscle fibers and visceral adipocytes from tilapia, compared to 28 or 30ºC. Red Tilapia, GIFT and Supreme strains show differences in muscle growth and adipose tissues in response to temperature of cultivation.